A STUDY OF CODE MIXING IN RADIO BROADCAST ON 99.60 FM PTPN RADIO IN SURAKARTA - SYAIFUDIN, MAKMUN (2011)
This research investigates code mixing in radio broadcast on 99.60 fm PTPN radio in Surakarta. The study aims to describe the forms of code mixing and to describe the reasons of using the code mixing. The data of this research are Indonesian-English code mixing occurred in broadcasting on 99.60 fm PTPN radio and the information about the reasons of using code mixing is from the broadcaster. The data are taken from 99.60 fm PTPN radio on first march by using recording and interview in collecting the data. The data are analyzed base on the linguistic forms and the reasons of using the code by employing the theory proposed by Ohoiwutun. The result of the research shows that there are seven forms of code mixing: word, blending, affixation, word reduplication, hybrid, phrase and clause. Moreover there are two reasons of using the code: need filling motive, and other reasons. Other reasons include three reasons, to refine, to give information and to show personal speaking habit.